-2/5(8y-2)=5(10-y)

Simple and best practice solution for -2/5(8y-2)=5(10-y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2/5(8y-2)=5(10-y) equation:



-2/5(8y-2)=5(10-y)
We move all terms to the left:
-2/5(8y-2)-(5(10-y))=0
Domain of the equation: 5(8y-2)!=0
y∈R
We add all the numbers together, and all the variables
-2/5(8y-2)-(5(-1y+10))=0
We multiply all the terms by the denominator
-((5(-1y+10)))*5(8y-2)-2=0
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+10)))*5(8y-2), so:
(5(-1y+10)))*5(8y-2
We calculate terms in parentheses: -((5(-1y+

See similar equations:

| (4x+20)=(7x-1) | | -91=11x | | 91=11x | | (4x+20)+(7x-1)+x=180 | | 5(x-4)(x+3)(2x-1)=0 | | 9(p+)=5p-1 | | 25-7x=x+1 | | 4.9t^2+5t-100=-0 | | 25–7x=x+1 | | 6x+20=46 | | n2-9n=90 | | 7m+29(=2m+9 | | 38=-6w+2w | | 7(q–5)=–63 | | -12s-48=-60 | | 0.75(-8v-4)=2(v+6)-3v | | 5x(4x-3)(2x+7)=0 | | 11m-8-6m=23 | | --9(1-5c)=-(-9c+9) | | x^2+13x+82=0 | | 2x^2-24x-36=0 | | 2/x^2-x=1/x-1 | | 2/x^2=1/x-1 | | 9+3n=2 | | 2(-5x-12)=11-87 | | 2x-14-x=711 | | |3v=5|=8 | | (6x-18)=42 | | 0.75(15-6y)-7=-11 | | 5x-8(x+5)=6=3x | | 0.4y-4=2* | | 7x+27=6x+36 |

Equations solver categories